An unusual case of ear mould impression material as a foreign body in the middle ear: case report. Issue 3 (26th March 2021) - Manjunath, D; Vadlamani, S; Gaur, S K; Dutt, S N
Abstract: Background: The occurrence of retained ear mould impression material is rare and can lead to complications. The current case report describes one such complication, where the silicone impression material used to take the impression of the ear canal flowed into the middle ear through the pre-existing tympanic membrane perforation. Five days later, the patient presented with worsened hearing and blood-tinged discharge from the ear. Ear microscopy revealed a greenish foreign body in the middle ear. Case report: The foreign body was removed by tympanotomy and the perforation repaired using a temporalis fascia graft. A hearing aid was prescribed after ensuring that the perforation had healed. Conclusion: It is essential that the audiologist perform a basic otological examination before prescribing a hearing aid and preparing an ear mould. A clinical approach algorithm for audiologists, for prior to taking an impression, is suggested.